2017
DOI: 10.1177/0194599817717458
|View full text |Cite
|
Sign up to set email alerts
|

Lengthening Temporalis Myoplasty: Objective Outcomes and Site‐Specific Quality‐of‐Life Assessment

Abstract: Objective Evaluate outcomes of the lengthening temporalis myoplasty in facial reanimations. Study Design Case series with planned data collection. Setting Ospedali Riuniti, Bergamo, and AOUC Careggi, Florence, Italy. Subjects and Methods From 2011 to 2016, 11 patients underwent lengthening temporalis myoplasty; demographic data were collected for each. Pre- and postoperative photographs and videos were recorded and used to measure the smile angle and the excursion of the oral commissure, according to the SMILE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…Comparable results have been reported in the literature [7]. The low complication rates described in the literature were confirmed in this study [7, 11-14].…”
Section: Discussionsupporting
confidence: 91%
“…Comparable results have been reported in the literature [7]. The low complication rates described in the literature were confirmed in this study [7, 11-14].…”
Section: Discussionsupporting
confidence: 91%
“…This is consistent with our study in which LTM increased lip force by a mean of 1.55 times. Panciera et al (18) assessed disability using the Facial Disability Index (FDI) and demonstrated significant improvement in disability, with the FDI score increasing from 33.4 points to 49.9 points i.e. an improvement of 33% (p < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…The vertical and horizontal smile symmetry were assessed for each patient. Photographs were initially standardized by comparing white to white iris diameter against the standard human reference value 9 of 11.7 mm to obtain a multiplication factor 10 using Adobe Photoshop CC v20 (Adobe, San Jose, CA, USA). An inter-pupillary line (IPL) was drawn and from the midpoint of the IPL, a perpendicular line was dropped down to the chin point.…”
Section: Methodsmentioning
confidence: 99%